Influence of aquaculture effluents on the growth of Salvinia molesta - Pistori,Raquel Eduarda Trevisan (2010)
OBJECTIVE: Aquaculture generates social and economic benefits, but also causes impacts on the environment. One of the major impacts is the release of untreated effluents into rivers, reservoirs, and lakes, which can affect aquatic populations and communities. In this study, we tested the hypothesis that effluent from aquaculture favors the growth of the floating aquatic macrophyte Salvinia molesta; METHODS: The study was carried out in a non-impacted reservoir (NIR) and in another reservoir (IR) that is impacted by discharges of aquaculture effluents, and lasted for nine months. In each of the reservoirs, we installed four experimental units containing 10 ramets of S. molesta. Monthly, we measured limnological variables of the water and the biomass of S. molesta in both reservoirs; RESULTS: The temperature, turbidity, electrical conductivity, alkalinity, chlorophyll-a, total Kjeldahl nitrogen, and total phosphorus were higher in the IR in all the collection months. At the end of the experiment, the concentrations of total nitrogen and phosphorus in the biomass of S. molesta from the IR were higher than those in plants from the NIR. The estimated support capacity (K) for S. molesta in the NIR was 3.0 ± 0.7 g DM.m-2 and in the IR was 37.4 ± 2.4 g DM.m-2; CONCLUSIONS: It was concluded that the discharge of aquaculture effluent modifies the limnological characteristics of the water of the receiving reservoir, and that the growth of Salvinia molesta is favored by the aquaculture effluent, because of the increases in the concentrations of nitrogen and phosphorus in the water.